Genetic diversity among some important poultry species by using randomly amplified polymorphic DNA markers - SHARMA, DEEPAK; APPA RAO, K B C; TOTEY, S M (The Indian Journal of Animal Sciences, 2014)
The potential use of randomly amplified polymorphic DNA (RAPD) was evaluated as a source of genetic markers for studying variation among poultry species, viz. chicken, quail, guineafowl and turkey and to establish genetic relationship among them. Random decamer primers (32) were tested, 29 of these primers generated species specific pattern. The 4 species were distinct in RAPD pattern. Out of 696 amplicons which were scored, 95 % were polymorphic suggesting high amount of polymorphism between the species. The genetic similarity between the species measured by band sharing(0.326 to 0.395) and Jaccard's similarity codficient (0.208 to 0.272) revealed that these species are separated at low correlation values. The genetic distances estimated from band sharing frequency (0.998 to 1.236) showed that Â·these species are distant from each other. The phylogenetic relations among these poultry species based on Jaccard's similarity coefficient also revealed the similar pattern. The results suggest that RAPD can be used as a powerful tool for species< identification, estimation of genetic relationship and molecular systematic analysis in the poultry species.